Hak Kebebasan Beragama Dalam Pasal 28 I Ayat 1 UUD 1945 Perspektif Politik Propetik - Rifa'i, Iman Jalaludin (Edulaw : Journal of Islamic Law and Yurisprudance, 2021)
Freedom of religion in Indonesia has become a shared commitment, this is enshrined in the 1945 Constitution and Law Number 39 of 1999 concerning Human Rights. However, in practice there are still violations, this happens that there is an imbalance between the rules and law enforcement. So this study discusses how the freedom of diversity in the 1945 Constitution is viewed from prophetic political values; humanization (ta'muru bil ma'ruf), liberation (tanhawna 'anil munkar), and transcendence (tu'minu billah). This research is normative legal research or library research, which examines applied research through data collection or scientific writing work whose object or data collection is the library. This research concludes that the right to freedom of religion as regulated in Article 28 I paragraph 1 of the 1945 Constitution is in accordance with the spirit of the basic values ​​of prophetic politics, namely liberation, humanization and transcendence.